Classification of BINUS University Student Organizations’ Logos from the Perspective of Visual Construction - Sonia, Candi Reggi; Lakonawa, Petrus (Social Economics and Ecology International Journal, 2019)
This research focuses on the classification of BINUS University student organizations’ logo using textual qualitative approach. It aims at analyzing how they chose the shape of the logo in order to express their identity. This research is framed by three significant focal points in view of its construction namely, the combination of picture mark and letter mark, the integration of picture mark within letter mark or vice versa, and letter mark only. The result of this research shows that the officials of the organizations tend to choose logo that has aesthetic quality in simple visual form rather than complicated one. This research also closely observes the making process of the logo and its classification up to its final appointment as the official logo of the student organizations.